Determination of evapotranspiration for cotton in Alabama by the Penman method. (2018) - Hasan, Mahbub; Kassu, Aschalew; Mentreddy, Srinivasa Rao
Cotton irrigation is increasingly becoming a challenge because of climate change effects such as the variations in rainfall, temperature, and cloudiness during the growing season. Cotton crop characteristics, as well as the prevailing environmental conditions, are critical in determining cotton water use. An efficient method of scheduling irrigation to cotton crop is imperative for optimising time and amount of water to apply for achieving cotton yield potential. In this article, a reliable approach to determine crop water requirement for cotton cultivation is proposed using the Penman method for Gadsden, Alabama, located in the southern part of the USA.